MUGABE GOVERNMENT SURVIVAL STRATEGIES - Korai Pinheiro Minillo, Xaman (2024)
The main objective of this article is to explain how Robert Mugabe's regime in Zimbabwe has been sustained, in the face of the calamitous situation in which the country finds itself, highlighting the role of the international environment in the Government's survival strategies. Devoid of many material resources of power, Mugabe develops in his foreign policy an identity and a discourse that guarantee him the support of international partners, mainly regional, and underlies a certain internal legitimacy, thus contributing so that he remains in the control of the State.